PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SEKOLAH DASAR - Mohd Khairul Aswadi; Musnar Indra Daulay; Ramdhan Witarsa; Fadhilaturrahmi; Rusdial Marta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low Critical Thinking Ability of students in class V of SDN 001 Bangkinang. One solution to overcome this problem is to use the Talking stick Type Cooperative model. This research method is Classroom Action Research (PTK) which is carried out in two cycles consisting of two meetings and four stages, namely implementation planning, observation and reflection. When this research was carried out in October 2024. The subjects of this research were class V students at SDN 001 Bangkinang. Consisting of 12 students, there are 5 male students and 7 female students. Data collection methods use observation techniques and documentation techniques. The research results show that using the Talking stick Type Cooperative learning model can improve students' critical thinking abilities. This is shown by the observation results obtained in each cycle I meeting I from 12 students, it is known that the critical thinking skills of students included in the complete category reached 4 people or 34% and cycle I meeting II there were 5 people or 41%. Then in cycle II, meeting I, there were 7 people or 58% who had completed it and in cycle II, meeting II increased to 10 people or 83%. Through the application of the Talking stick Type Cooperative learning model to improve the critical thinking skills of class V students at SDN 001 Bangkinang.